Resistance to ionic pt insertion in oxygen excess LaMnO3 perovskite lattices and its effect in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2014)
Pt doped and impregnated LaMnO3 perovskites are synthesized at different temperatures and Pt and Mn states are compared in an attempt to get insight into extent of lattice incorporation of Pt in perovskite. Various characterization studies indicate that oxygen excess system like LaMnO3 presents substantial resistance to B site doping with Pt. This behavior is different from other oxygen deficient perovskites like LaCoO3 and LaFeO3 in which lattice incorporation stabilizes the active species against sintering. Water gas shift reaction was used as a probe reaction to understand the effect of this difference in the activity. In case of LaMnO3, failure in lattice substitution leads to sintering and deactivation at high synthesis temperatures (>= 700 degrees C) in both impregnated and doped samples. In doped samples, however, a strong interaction of Pt species with a persistent amorphous phase prevents sintering at lower synthesis temperature thereby enhancing the activity when compared to impregnated sample. The study reveals a possible mechanism in which only Pt(0) species is active with perovskite playing a minimal role in this system due to the resistance to lattice incorporation. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Oxygen excess; Perovskites; Water gas shift reaction; XPS; XRD

Role of oxygen vacancies in water gas shift reaction: activity study on BaCe0.98-xYxPt0.02O3-delta perovskites - Rajesh, Thattarathody; Devi, R. Nandini (Journal of Physical Chemistry C, 2014)
Oxygen vacancies are suggested to play an important role in reactions like water gas shift where the redox mechanism is crucial. Pt-doped BaCeO3 perovskite, moderately active for water gas shift reaction, is selected for further understanding the role of oxygen vacancies, since perovskite lattice can tolerate and stabilize vacancies facilitating an accurate quantification. Vacancies are created in the system by systematic doping of increasing amounts of Y. Structure and activity studies reveal that the 6% Y-substituted compound which has the most symmetric B site coordination environment exhibits the highest activity. Hence, it is not the extent of vacancies but their structural characteristics which are found to be decisive. Symmetric coordination around B ions facilitates water adsorption and dissociation by lowering the energy barriers due to the creation of an isotropic environment.

Role of B site ions in bifunctional oxygen electrocatalysis: a structure-property correlation study on doped Ca(2)Fe(2)O(5)brownmillerites - Thundiyil, Shibin; Vinod, C. P.; Kurungot, Sreekumar; Devi, R. Nandini (Physical Chemistry Chemical Physics, 2020)
The role of B site doping with transition metals in brownmillerites, a perovskite related family of compounds, in bifunctional oxygen electrocatalysis,viz., simultaneous reduction and evolution reactions, is analysed. Ca2Fe1.9M0.1O5(M = Mn, Co, Ni, and Cu) is synthesised and structurally characterised by powder XRD and Rietveld refinement. Valence states of the surface B site ions are identified by X-ray photoelectron spectroscopy. Bifunctional oxygen electrochemistry is studied with the RDE and RRDE techniques and correlated with the structural and electronic parameters like oxygen non-stoichiometry and B site catalytic activity. Since the widely accepted electronic descriptors like e(g)filling may not be sufficient for explaining the bifunctional activity, B site electron donating capability as well as the extent of oxygen vacancies enhancing O(2)adsorption is also considered. Such structural parameters are also found to influence both the ORR and OER and based on this, Ni doping is proposed as advantageous for the bifunctional activity.

Red fluorescent ultra-small gold nanoclusters functionalized with signal molecules to probe specificity in quorum sensing receptors in gram-negative bacteria - Chahande, Anurag M.; Lathigara, Disha; Prabhune, Asmita A.; Devi, R. Nandini (Archives of Microbiology, 2021)
Ultra-small (size < 2 nm) gold nanoclusters (AuNCs) are used as fluorescent probes which have excellent applications in bioimaging and sensing due to their emission in visible and NIR spectral region. Here, this property is exploited for understanding the quorum sensing phenomenon in bacteria which is regulated by signal molecules which are specific to various species. AuNCs are then functionalized with the signal molecules, Acyl Homoserine Lactones (AHL) of varying carbon chain length, C-6, C-8, and C-12 without 3rd C modification, to sense different strains of gram-negative bacteria i.e., Escherichia coli, Cronobacter sakazakii and Pseudomonas aeruginosa. In the concentration employed, selectivity to a limited extent is observed between the three Gram-negative bacteria tested. E. coli showed emission with all the AHL conjugates and P. aeruginosa did not interact with any of the three conjugates, whereas C. sakazakii showed specificity to C-8AHL. This is probably due to selectivity for cognate AHL molecules of appropriate concentrations.
Keywords: acyl homoserine lactone; fluorescence imaging; Gold nanoclusters; quorum sensing; Receptors; selectivity

Remarkable SO2 and H2S resistant ability on CO oxidation by unique Pd/WO3 3D hollow sphere nanocatalyst: correlating structure-activity relationships on SO2 exposure - Jeyavani, Vijayakrishnan; Kondhekar, Deepali; Bhati, Meema; Dev, Sahil; Joshi, Kavita; Devi, R. Nandini; Mukherjee, Shatabdi Porel (ACS Applied Energy Materials, 2024)
We report a simple inorganic route for synthesizing a Pd/WO3 3D hollow sphere nanocatalyst, where Pd nanoparticles are encapsulated and well distributed on porous tungsten oxide nanospheres. The synthesis protocol has advantages, as it requires no surfactant or stabilizing agent, Pd loading is easily tuned, and the as-synthesized nanomaterials can be directly used as catalysts for the CO oxidation reaction. The synthesized nanocatalyst exhibited 100% CO to CO2 conversion efficiency at 260 degrees C. In addition, the nanocatalyst demonstrated remarkable SO2 (3 ppm) tolerance during the CO oxidation reaction for prolonged SO2 sulfation of 1-21 h at 260-400 degrees C. This represents the longest SO2 exposure time reported to date based on a single metal Pd/support-based nanocatalyst. No decrement in CO conversion efficiency was observed even after SO2 (3 ppm) treatment for 21 h for the first time based on a single metal Pd-based nanocatalyst. Moreover, the synthesized nanocatalyst shows H2S (4 ppm), even in situ H2S tolerance during the CO oxidation reaction at 260 degrees C for 1-3 h and exhibited less sensitivity to prolonged and stringent sulfur exposure, with the highest H2S concentration and maximum 100% CO to CO2 conversion efficiency obtained after H2S treatment for the first time based on a Pd-based nanocatalyst to the best of our knowledge. The composition and structure of the R-Pd/WO3 nanocatalyst were not much influenced, even after the prolonged SO2 and H2S exposure during the CO oxidation reaction, as verified from spent catalyst analysis. Finally, our DFT-based model provides insights into understanding the observed sulfur resistance on Pd/WO3 by analyzing the underlying electronic structure. Therefore, our strategic synthesis methodology will open up many opportunities to select Pd/metal oxide-based nanomaterials for designing highly efficient, stable, and SO2/H2S-resistant nanocomposite catalyst.
Keywords: CO oxidation; DFT calculation; nanocatalyst; palladium (Pd); SO2 andH(2)S resistant ability; structure-activityrelationships; tungstenoxide (WO3)